1998
DOI: 10.1007/bf02815857
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside composition of a mouse brain tumor grown in the severe combined immunodeficiency (SCID) mouse

Abstract: The content and composition of gangliosides were examined in an experimental mouse brain tumor, EPEN, that was grown subcutaneously in the flank of the syngeneic C57BL/6J (B6) host and in the B6 severe combined immunodeficiency (SCID) host. SCID mice lack functional T- and B-lymphocytes, but have a normal complement of macrophages. The content and distribution of the brain tumor gangliosides were similar whether the tumor was grown in the immunocompetent B6 host or in the B6-SCID host. N-acetylneuraminic acid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…We previously showed that most NeuGc-containing gangliosides present in mouse brain tumours and in human glioma xenografts are derived from tumour-associated host cells (macrophages) and from the mouse serum (Ecsedy et al, , 1999Seyfried et al, 1998). Since most NeuGc-containing gangliosides in mouse serum are synthesized in the liver (Cotterchio and Seyfried, 1994), we suggest that the marked reduction of NeuG-containing gangliosides in the i.c.-grown brain tumours results in large part from the NB-DNJ-induced inhibition of ganglioside biosynthesis in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that most NeuGc-containing gangliosides present in mouse brain tumours and in human glioma xenografts are derived from tumour-associated host cells (macrophages) and from the mouse serum (Ecsedy et al, , 1999Seyfried et al, 1998). Since most NeuGc-containing gangliosides in mouse serum are synthesized in the liver (Cotterchio and Seyfried, 1994), we suggest that the marked reduction of NeuG-containing gangliosides in the i.c.-grown brain tumours results in large part from the NB-DNJ-induced inhibition of ganglioside biosynthesis in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…GM3 is the only ganglioside synthesized by cultured EPEN cells, while gangliosides in the 'a' metabolic pathway (GM3, GM2, GM1, GD1a) are the major gangliosides synthesized by cultured CT-2A cells. Most other gangliosides in the tumours are derived from tumour-infiltrating host cells or from the serum (Seyfried et al, 1996;Ecsedy et al, 1998;Seyfried et al, 1998). The significant reduction in total ganglioside content in the NB-DNJ-treated tumours (Table 1) was associated with a noticeable shift in ganglioside distribution from the structurally simple (GM3) to the structurally complex gangliosides (GD1a, GT1b) ( Figure 5).…”
Section: Influence Of Nb-dnj On Tumour Liver and Brain Ganglioside Dmentioning
confidence: 96%
“…In marked contrast to the U87‐MG xenograft, only trace levels of NeuGc‐containing gangliosides were found in the U87‐MG cultured cells. Previous studies showed that low levels of NeuGc‐containing gangliosides in cultured mouse and human tumor cells were derived exogenously from NeuGc‐containing gangliosides in bovine serum (Hof and Faillard, 1973; Furukawa et al, 1988; El‐Abbadi and Seyfried, 1994; Seyfried et al, 1998). Kawashima and co‐workers (1993) also found that NeuGc‐containing gangliosides in human melanoma xenografts grown in nude mice were derived from the uptake and metabolism of NeuGc‐containing gangliosides present in the nude mouse plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The GSL composition of brain tumors differs markedly from that of normal brain. This arises from GSL abnormalities in proliferating tumor cells and from tumor‐infiltrating host cells (Seyfried et al, 1996, 1998). The enrichment of GSLs on the cell surface and their considerable structural diversity make them potential targets for tumor immunotherapy and diagnosis (Irie and Morton, 1986; Murray et al, 1994, 1996; Sung et al, 1994; Wikstrand et al, 1994 a , b ; Suetake et al, 1995; Uttenreuther Fischer et al, 1995; Nishinaka et al, 1996).…”
mentioning
confidence: 99%
“…Subcutaneous injection of an experimental ependymoma incapable of synthesizing endogenous GM2(Neu5Gc) results in a tumor that contains GM2 (Neu5Gc) as well other gangliosides suggestive of the presence of Neu5Gc-expressing macrophages [89]. These Neu5Gc-containing gangliosides are still found when the cells are injected into mice with severe combined immune deficiency (SCID), which have no B or T lymphocytes, further suggesting that the gangliosides present do originate from tissue macrophages and/or from metabolic uptake by the tumor cells [90]. To date, no characterization of naturally occurring neural tumors has demonstrated endogenous Neu5Gc synthesis.…”
Section: Claims For Presence Of Neu5gc In Neural Tissuesmentioning
confidence: 99%